P-glycoprotein- and organic anion-transporting polypeptide-mediated transport of periplocin may lead to drug–herb/drug–drug interactions - Liang S; Deng FC; Xing HY; Wen H; Shi XY; Martey ON; Koomson E; He X (Dove Medical Press, 2014)
Sheng Liang,* Fengchun Deng,* Haiyan Xing, He Wen, Xiaoyan Shi, Orleans Nii Martey, Emmanuel Koomson, Xin He School of Chinese Materia Medica, Tianjin University of Traditional Chinese Medicine, Tianjin, People's Republic of China*These authors contributed equally to this workAbstract: Periplocin, an active and toxic component of the traditional Chinese herbal medicine Periploca sepium Bge, is a cardiac glycoside compound that has been implicated in various clinical accidents. This study investigated the role of transporters in the intestinal absorption and biliary excretion of periplocin, as well as the possible metabolic mechanism of periplocin in liver S9. In a bidirectional transport assay using Madin–Darby canine kidney (MDCK) and MDCK multidrug-resistance protein (MRP)-1 cell monolayers, both in situ intestinal and liver-perfusion models were used to evaluate the role of efflux and uptake transporters on the absorption and biliary excretion of periplocin. In addition, in vitro metabolism of periplocin was investigated by incubating with human/rat liver S9 homogenate fractions to evaluate its metabolic mechanisms in liver metabolic enzymes. The results showed that P-glycoprotein (P-gp) was involved in the intestinal absorption of periplocin, whereas MRP2 and breast cancer-resistance protein were not. The efflux function of P-gp may be partly responsible for the low permeability and bioavailability of periplocin. Moreover, both inhibitors of P-gp and organic anion-transporting polypeptides (OATPs) increased periplocin biliary excretion. No obvious indications of metabolism were observed in the in vitro incubation system, which suggests that periplocin did not interact with the hepatic drug metabolic enzymes. The results of this study showed that the efflux and uptake transporters P-gp and OATPs were involved in the absorption and biliary excretion of periplocin, which may partially account for its low permeability and bioavailability. As a toxic compound, potential drug–herb/herb–herb interactions based on OATPs and P-gp should be taken into account when using P. sepium Bge in the clinic.Keywords: periplocin, P-gp, OATPs, toxicity, interactions